Persinggungan dalam Rampokan; Apresiasi Komik karya Peter Van Dongen - Terra Bajraghosa (DeKaVe, 2014)
Rampokan Jawa & Selebes, is a comic created by Peter Van Dongen, telling a story about Johan Knevel, aDutch soldier, in his mission looking for Ninih, his childhood nanny back in Netherland-Indies. This comic attractedmany Indonesian readers because of two aspects. First, the setting is in Indonesia around the year 1946-1947, whichprovides readers with old time indis architectures and vintage designs of things. The second one is its clear line style,similar to Herge’s ‘Tintinesque’ style. These tendecies may appear as pseudo-appreciation to the medium.This essay’s goal, departed from Rampokan’s intersection with Tintin, and Indonesia history setting, is to find out theproportionally apreciation on comic as a medium. According to David Carrier, one of comic aesthetic quality relies onthe ability of the readers to project their desires on the comic they read. In creating the story, comic compositioninvolved the power of color and visual art syle choice to deliver the idea of the story.From the discussion, two things about Rampokan appreciation are apprehended. The location and time settingvisualization which based on deep research became the main power of this Rampokan comic; representing narrativeenvironment that projected reader’s desire: the detailed visualization of the young Indonesia. The choice of clear linestyle, combined with color composition as an emblematic presentation enabled the delivery of multi plots narratives.Combination of the setting as an observation result and detail art style, provide readers to reasonably believe the storyworldcreated by Peter Van Dongen. Rampokan’s appreciaton quality based on the well-crafted storytelling throughwell-constructed story-world which enabled readers to follow its fictional or even surrealistic plot twistsunconditionally.Keywords: Comic, Appreciation, Aesthetic, Rampokan Jawa & Selebes